Propaganda, entertainment and education on children´s programmes in the radio broadcast of the Canary Islands during the Franco’s regime, 1939-1975 - Yanes Mesa, Julio Antonio (Historia y Memoria de la Educación, 2016)
Children’s programmes in the Canary Islands’ radio broadcasting were not isolated from the propaganda used by the media towards children and adolescents in cultural, educational and even ludic spheres during Franco’s regime. However, with respect to the authorship of the programmes, the government’s proselytizing zeal was limited to the tape-recorded broadcasts brought from the Peninsula and those produced by the regime’s local activists; as for transmissions produced by local broadcasters, they increasingly revolved around apolitical contents, and in the case of the educational programs, contents were focused on the use of methodologies we can consider antagonistic to the propaganda promulgated by the dictatorship’s ideologists. Contextual reasons such as the distance from Madrid, the liberalism inherent in the insular idiosyncrasy and the incompatibility of the autocratic thesis of Franco’s regime with the traditional openness to foreign trade in the islands help to explain the appearance of these discordances in such an outlying region as the Archipelago. These same reasons allow us to understand the paradox of the most innovative achievements in the educational field being carried out by broadcasts with an audience that was considerably smaller and, therefore, less prone to be under the scrutiny of the censors at the time.